Using GIS for Identification of Potential Ecotourism Sites: A Case Study of Jamui District of Bihar: Unleashing the Ecotourism Potential of Jamui District in Bihar (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The primary focus of nodal tourism development agencies is on the development of pilgrimage (Buddhist, Jain) destinations, while the ecotourism site development initiatives have taken a back-seat, in the on ground implementation of the policy. The major natural areas of the state having good potential to become ecotourism sites are pristine and untouched by tourism activities. The present study aims to identify the potential ecotourism sites in the Jamui district of Bihar, using Geographic Information Systems. The 1992 Rio declaration and Agenda 21 focuses on special objectives, and the ways to be followed to pursue these objectives. The special objectives are related to solving spatial problems, while the ways implies sharing knowledge for collaborative, transparent, and participatory decision making. In planning, decision-making, and management GIS is considered most advance tool available to deal with complex problems- the spatial problems- in a balanced mediation of economic, environmental, and social objectives. It is an essential tool though, which, when properly used, may offer effective support to geospatial planning and decision making, because the geographical components are the key elements, while dealing with sustainable development. In spite of having variety of tourism opportunities, from, destinations of religious and spiritual interest like Kakan and Lachuar to the picturesque scenic locations of Simultala to the places of historical interest like Gidhour Fort and Minto tower the district has failed to harness its tourism potential. It has meagre share in the overall tourist arrivals (domestic and foreign) to the state of Bihar. It is essential to create congenial environment through confidence building among the local community and socially excluded and economically deprived communities through tourism as an agent and to attract those who have chosen the path of violence to bring them back into the mainstream.